Ecological and faunistic analyse parasites of Raccon (Procyon lotor L.) in different zones of Azerbaijan - A. A. Azizova (Юг России: экология, развитие)
134 racoons (Procyon lotor) acclimatired in Azerbaijan were analysed with full helminthological section to study of parasitofauna, distribution of parasites on groups, species composition, ecology and biology, epizootological and epidemiogical role. Researches were carried out within 2001-2007 in 4 different zones (Sheki-Zagatala, Guba-Khachmaz, Shamakhi- Ismailly, Lenkoran-Astara) of Azerbaijan. Researches were resulted in recording of 2 species of lower animals, 23 species of helminthes and 11 species of ectoparasites.